Effectiveness of Thermos to Maintain the Temperature of Ringer Lactate and Normal Saline 0.9% at AC Temperature 18˚C - Rifda Nur Achriyana Arif; Abdurrahman Wahid; Ifa Hafifah; Gia Eka Negara (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
Hemorrhagic shock patients require fluid resuscitation, but extra efforts should be made to provide 39 C fluids to avoid hypothermia. One of the media to maintain temperature is a thermos. The purpose of this research is to identify whether the flasks can keep 39-degree crystalloid fluids at 18 degrees Celsius. This study used a pre-experimental method, with One-Shot Case Study type, 12 bottles of crystalloid liquid was warmed to 39°C, then put into 2 rice flasks, and temperature changes were measured for 6 hours at AC temperature 18˚C. The study was conducted on 30 November 2019. The findings show that temperatures in 6 bottles of RL liquid decreased by 6.8 -7.4 C and in 6 bottles of NS 0.9% liquid decreased by 5.3 - 6.4 C. Statistical results using the Mann-Whitney p-value is 0,000. It was concluded that there was a significant difference between changes in temperature of lactate Ringer's fluid and normal saline 0,9%. A thermos can maintain a temperature of 39˚C for about 1 hour and can prevent hypothermia from reaching 36˚C for about 3 hours.